Mulher e patriarcado na mídia: O jogo discursivo das revistas VEJA e IstoÉ. - Reis, Hevelin Bentes (Brasil, 2022)
The present study aims to bring a discussion about journalistic practice from the discourse found in journalistic content of VEJA and IstoÉ magazines and, thus, understand the functionality of the journalistic system, as an ideological device, reinforcing stereotypes in particular, about the image of women. For this reflection, we worked with the theory of Discourse Analysis (AD) of French line in the perspective of Souza (2014) and Orlandi (2002), as a theoretical-methodological framework, which uses a qualitative approach in the analyses. Through it and the premises that outline journalism, according to Ramonet (2013), Lage (2001), Traquina (2005) and Silva (2013), in addition to the theoretical framework on the representation of women in the media, it was possible to perceive, in both reports used as corpus of study “Marcela Temer: beautiful, demure and homely” and “A president outside of herself”, as the media manages to discursively construct, the maintenance of female beauty standards. Thus, there was a journalistic tendency to maintain, in the discourse, ideological formations that delay the overcoming of machismo in Brazilian society. Such conduct of the journalist subject contradicts the essence of journalism, established in the Code of Ethics of Brazilian Journalists, creating a crisis of credibility in journalism before the public.